Métodos ágeis, dilema e rerroupagem no desenvolvimento de jogos educacionais em sala de aula - Ferraz Junior, Wilton Moreira (Universidade Federal de São Carlos, 2015)
This work aims to develop a novel method to design educational games, following Extreme Programming and Scrum Agile Methods and screenplays under the dilemmas and mechanical game re-guise concepts, which are already widely accepted in the literature. Workshops using the proposed method were conducted in order to identify the demands of educators and students from elementary and middle school and also the viability in the implementation of the method as a support tool to the teaching process. The validation results and the method acceptance were evaluated by statistical tests, which are also widely explored in the literature for similar samples. The final remarks show the successful methods evolution and their validation results under the considered classrooms context.
Agile methods, dilemmas, and re-guise concepts for educational games development in classroom
Keywords: jogos sérios (Serious Game); produção de jogos educativos; metodologias ágeis; método computacional; desenvolvimento ágil de software; jogos educativos; serious games; educational game design; agile methods; computational methods; teaching learning-processes; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO